Disease Management in Maize - Shekhar, Meena; Kumar, Sangit; Kumar, Shrvan; Hooda, K. S. (Indian Farming, 2015)
The success and sustainability of IDM strategy, especially with resource poor farmers greatly depends on their involvement in helping generate location specific techniques and solutions suitable for their particular farming systems and integrating control components that are ecologically sound and readily available to them. Training and awareness of farmers, disease survey teams, agricultural development officers, extension agents and policy makers continue to be an important factor for the successful implementation of management strategies on sustainable basis. All direct stakeholders including farmers, extension workers, and local crop protection technicians should have a practical understanding of the ecology, etiology and epidemiology of the major diseases of maize.